(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article is about some tools of teaching, the role of teacher’s in class is described directly, Teacher-Centered Approach to Learning, Teachers are the main authority figure in this model. Students are viewed as “empty vessels” whose primary role is to passively receive information (vialectures and direct instruction) with an end goal of testing and assessment.